Bermain Bolavoli gandu untuk Kesegaran Jasmani Siswa - Asim Asim (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1999)
The study aims to examine the effects of volleyball games on students’ physical fitness. This experimental study included Gandu Volleyball and Mini Volleyball with game-part-game and part-game instructional patterns. Forty students of Karanggandu Elementary School were involved, comprising twenty boys of grade 5 and twenty boys of grade 6. The results of two-way analysis of variance and Tukey tests indicate that Gandu Volleyball is better than Mini Volleyball for students’ physical fitness in the game-part-game instructional pattern, but there is no significant difference between the two in the part-game instructional pattern. There is an effect of interaction between instructional pattern and types of volleyball games on students’ physical fitness.